2021
DOI: 10.4103/jfmpc.jfmpc_493_21
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the perceptions of family members patients hospitalized in intensive and cardiac care units (CCU and ICU) in regard to the importance of family needs in Golestan University of Medical Sciences 2020

Abstract: Introduction: Intensive care units (ICUs) cause double stress and tension in hospitalized patients' family members. Improving care quality in these wards requires estimating the importance of the families' needs by the nurses. Therefore, the present research was designed to determine and compare the perceptions of family members of the patients hospitalized in the ICUs and cardiac care units (CCUs) about the importance of family needs and their relationship with some factors in the Golestan Univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…Item with highest mean score in our study on cognitive support was on support regarding provision of information and their professional opinion, this is contrary to findings in similar study (Emmamally & Brysiewicz, 2019) where families obtained low scores on this item. Previous studies of perceived needs of family members of hospitalized patients in Intensive and cardiac care units (Elay et al, 2020; Asemeh et al, 2021) reported that provision of information was considered as one of the most important needs of family members. Information serves as education and may enhance family coping skills and capability all through the hospital experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Item with highest mean score in our study on cognitive support was on support regarding provision of information and their professional opinion, this is contrary to findings in similar study (Emmamally & Brysiewicz, 2019) where families obtained low scores on this item. Previous studies of perceived needs of family members of hospitalized patients in Intensive and cardiac care units (Elay et al, 2020; Asemeh et al, 2021) reported that provision of information was considered as one of the most important needs of family members. Information serves as education and may enhance family coping skills and capability all through the hospital experience.…”
Section: Discussionmentioning
confidence: 99%
“…Family-centered nursing care approach recognizes these needs and creates opportunity for the health workers to team up with family members to identify appropriate supports to meet these needs (Emmamally & Brysiewicz, 2019). Studies have been conducted to identify the important needs of families of hospitalized patients in different parts of the world (Izadpanah et al, 2021; Botes & Langley, 2016; Hsiao et al, 2017; Kohi et al, 2016). In view of the challenges of family members of hospitalized patients, previous studies also acknowledged the need for support of family members when their loved ones are hospitalized (Emmamally & Brysiewicz, 2019; Dieperink et al, 2018;).…”
Section: Introductionmentioning
confidence: 99%